Evaluation of Learning the Performance of Some Basic Volleyball Skills According to Cognitive Risk Style Among Students Aged 14 Years - Ismaeel, Huada; Auad, Khmael (Journal of Physical Education, 2019)
The Study Aimed at evaluating the learning performance of some basic skills in volleyball according to cognitive risk style using learning cycle. The researchers used the experimental method applied on (20) fourth grade secondary school students aged 14 years.  A questionnaire was set for this purpose and many styles and tools were used specially using learning cycle with volleyball skills. The teaching program lasted for (8) weeks with two hours per week (45) minutes. The data was collected and treated using proper statistical operations to conclude that risk takers learned basic volleyball skills. Finally they recommended continuing performance evaluation based on experimental learning.